Pengaruh Konsentrasi Gliserin Terhadap Stabilitas Fisik Salep Kombinasi Ikan Gabus, Teripang Emas, Madu Kelulut, Sirih Hijau Dan Minyak Cengkeh - Salsha Fhadila; Mohamad Andrie; Wintari Taurina (Fakultas Farmasi Universitas Setia Budi, 2024)
Snakehead fish (Channa striata), golden sea cucumber (Stichopus hermanii), kelulut honey (Heterotrigona itama), green betel nut (Piper betle) and clove oil (Syzygium aromaticum) have a synergistic effect in wound healing. This combination of ingredients is formulated in an ointment because it has a long contact time on the skin, so it is expected to be effective in healing wounds. The diversity of compounds from each ingredient can affect and cause preparation instability. The addition of glycerin as a humectant is a way to maintain the physical stability of the preparation because it can reduce water evaporation from the preparation. The purpose of this study was to determine the concentration of glycerin which can produce an ointment with good physical stability. Variations in the concentration of glycerin used were 5% (F1) and 2.5% (F2), and then the physical properties and stability of the preparations were tested. The method used is the stability test of the intermediate at 30° ± 2° C/ 65% ± 5% RH for 6 months. The measurement parameters include organoleptic test, homogeneity, spreadability, adhesion, protection, and pH. The results of the physical stability test showed that formula F2 (glycerin 2.5%) was the most stable formula in maintaining spreadability and adhesion from the 0 to 1 month. All formulas were damaged before testing the stability of physical properties in the 3rd month, so this test was not continued in the 3rd and 6th months.